2004
DOI: 10.1038/labinvest.3700156
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 is required for dedifferentiation of retinal pigment epithelium following retinal detachment in mice

Abstract: Retinal pigment epithelial (RPE) cells dedifferentiate and undergo epithelial-mesenchymal transition (EMT) following retinal detachment, playing a central role in formation of fibrous tissue on the detached retina and vitreous retraction (proliferative vitreoretinopathy (PVR)). We have developed a mouse model of subretinal fibrosis with implications for PVR in which retinal detachment is induced without direct damage to the RPE cells. Transforming growth factor-b (TGF-b) has long been implicated both in EMT of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 50 publications
(80 reference statements)
7
101
0
1
Order By: Relevance
“…FITC-conjugated secondary antibodies were used to visualize the specific immunoreaction as previously reported. [34][35][36] Results…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…FITC-conjugated secondary antibodies were used to visualize the specific immunoreaction as previously reported. [34][35][36] Results…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…34 Briefly, under general anesthesia by pentobarbital sodium, i.p., a linear incision was made in the central cornea and the crystalline lens was removed. After the vitreous cavity was filled with 1.0% hyaluronan, the retina was gently removed with forceps without damaging the pigment epithelium.…”
Section: Mouse Pvr Model and Adenoviral Gene Introduction Of Dn-p38mapkmentioning
confidence: 99%
“…Indeed, loss of Smad3 attenuates PVR in vivo, 87 and Smad7 gene introduction actually does suppress PVR in mice (S Saika, unpublished data, 2005).…”
Section: Gene Introduction To Suppress Emt and Subsequent Tissue Fibrmentioning
confidence: 99%
“…[12][13][14] Blocking signaling mediated by Smad2/3, the cytoplasmic signaling intermediates specific for TGF-b/ activin, is effective in inhibiting injury-induced tissue fibrosis in many tissues, such as skin, kidney, and the lens and retina of the eye. [15][16][17][18][19][20][21][22][23][24][25][26] We have recently revealed that both topical administration of SN50, an inhibitor of NF-kB signal, and adenoviral gene introduction of the Smad7, an inhibitory Smad that blocks Smads2/3, block tissue destruction in an alkali-burned cornea in mice (Saika et al, 2004 24,35 ).…”
mentioning
confidence: 99%